Analisis Pengelolaan Arsip Kepesertaan Inaktif Pada BPJS Ketenagakerjaan - Deverin Dwi Purwanti; Henry Eryanto; Suherdi Suherdi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The background of this research is based on the importance of good management of inactive participant archives to support the smooth running of administrative services, considering that inactive participant archives still have utility value, especially as evidence of claims and participant audits. This research has the objectives of (1) Knowing the principles of organizing inactive participant archives at BPJS Ketenagakerjaan Jakarta Rawamangun. (2) Knowing the filing/storage system for inactive participant archives at BPJS Ketenagakerjaan Jakarta Rawamangun. (3) Knowing the role of archivists/archive officers at BPJS Ketenagakerjaan Jakarta Rawamangun. (4) Knowing the obstacles and solutions carried out in managing inactive participant archives at BPJS Ketenagakerjaan Jakarta Rawamangun. The research method used is a descriptive method with a qualitative approach, through observation, interview, and documentation study techniques. The results of this study (1) The principle used by BPJS Ketenagakerjaan Jakarta Rawamangun is a combined principle, because the storage of active archives and inactive archives is carried out separately, active archives are in the membership room while inactive archives are in the archive room. (2) BPJS Ketenagakerjaan applies a numeric system by sorting the Company Registration Number (NPP) from the smallest to the largest so that it is easy to find archives when needed. (3) The role of archivists is very much needed, but in BPJS Ketenagakerjaan Jakarta Rawamangun there is a streamlining of the organizational structure resulting in the absence of archivists within it. (4) Archive management is still faced with several obstacles, such as limited storage space, still carried out manually, and a lack of workers with special competencies in the field of archiving. BPJS Ketenagakerjaan Jakarta Rawamangun Branch has also attempted to overcome these obstacles by digitizing participant archives, although the implementation has not been fully integrated into an adequate electronic archive management system. The conclusion of this study is the need to increase the capacity of human resources in archiving, optimize storage space and facilities, and develop an integrated digital system to achieve more effective and efficient management of inactive membership records.